2014
DOI: 10.2355/isijinternational.54.2446
|View full text |Cite
|
Sign up to set email alerts
|

Coking Technology Using Heavy Oil Residue and Hyper Coal

Abstract: Oil sand bitumen and hypercoal are examined as a caking additives to the mixture of strongly coking coal and non-slightly coking coal. Samples were coked, then their strength, crystallinity of the carbon structure, and an anisotropic microstructure were measured. Oil sand bitumen addition enhanced strength, but 15% addition caused a strength decline because of the formation of large pores and cracks. Hypercoal addition increased strength with increased its content. Correlation was observed between increased st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The soluble fraction contained THF, 1-MN solvent and 1-MN soluble coal fraction. 3,6,9,19,20,[25][26][27]32) As can be seen from the Fig. 1, in the case of THF wash approach, 1-MN soluble coal fraction and insoluble fraction are separated.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…The soluble fraction contained THF, 1-MN solvent and 1-MN soluble coal fraction. 3,6,9,19,20,[25][26][27]32) As can be seen from the Fig. 1, in the case of THF wash approach, 1-MN soluble coal fraction and insoluble fraction are separated.…”
Section: Methodsmentioning
confidence: 89%
“…3,5,[6][7][8][9]27,29,31) They investigated the interactions between caking and slightly caking or non-caking coals using NMR analysis and H/C ratio and concluded that the binders (HPC) enhance the thermo-plasticity of the coal blend due to their high thermo-plasticity and overlapping thermoplastic temperature range with that of coals. 3,[19][20][21][23][24][25][26][27] Sakimoto et al introduced carbon matrix connectivity index to estimate the coke drum index which directly correlates with the coke strength. 3,29) They concluded that the addition of binders (HPC) increase the carbon matrix connectivity of the coke leading to increased coke strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I D3 /I G ). 1) Table 2 summarizes the Raman parameters and its strength in the case of Tarrawonga coal, and photographs for the sample shape are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…We have investigated the relationship between the macroscopic structure including caking property and strength, and the microscopic structure of coke by Raman spectroscopy. So far, we have found that hypercoal (HPC) showed the most good nature among various binders, 1) for which shows large number of polycyclic naphthenes or aromatic compounds, low ash content, high softening and melting property. HPC is produced by a solvent extraction of coal and sequential drying, and it includes much polycyclic naphthenes and aromatics, less ash, and has high softening and melting property.…”
Section: Introductionmentioning
confidence: 99%